Assessment of Outcomes Following Distal Femoral Fractures Treated with Locking Compression Plate Fixation - Dr. R.Aswin Sundar; Dr. Yeshwanth Subash (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Fractures of the distal femur are relatively rare but pose significant challenges due to their complex nature. High-speed road accidents are a common cause in younger individuals, while falls at home often lead to these fractures in the elderly, especially in osteoporotic populations. Locking Compression Plates (LCPs) offer advantages in providing stability and promoting successful outcomes in treating these fractures. The goal of the current research is to examine the functional and radiological outcomes of Open Reduction and Internal Fixation (ORIF) of distal femur fractures utilizing a distal femur locking plate. Materials and Methods: This prospective research has been done at Saveetha Medical College and Hospital in Chennai from March 2022 to March 2023 including 30 skeletally mature patients having distal femur fractures. Patients who had fractures in the ipsilateral limb other than the distal femur or open-grade distal femur fractures were not included.A distal femur-LCP was used for fixation after fractures were manually reduced under direct observation. Postoperatively, patients underwent rehabilitation and follow-ups at regular intervals. Results: The study included 30 patients with fractures to the distal femur, with a mean age of 40.3 years and a distribution of fractures resulting from various causes. All patients achieved full weight-bearing postoperatively, with 14.8 weeks being the average period to union. The average postoperative knee flexion was 107.7°, with excellent or good outcomes observed in the majority of cases. Complications included early superficial infections and one case of varus malunion and limb length discrepancy, which required revision surgery. Conclusion: Managing distal femur fractures by utilizing a distal femur locking plate yields favorable outcomes, especially in Type A and C fractures and cases involving osteoporosis and peri-prosthetic fractures. While challenges exist, adherence to fundamental principles of fracture fixation and precise positioning of the implant can lead to satisfactory results. Continued research and refinement of surgical techniques are essential for optimizing outcomes in treating fractures to the distal femur.